2011
DOI: 10.1002/chem.201100866
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Mg–Zn Hybrid Chemistry: Inorganic Salt Effects in Addition Reactions of Organozinc Reagents to Trifluoroacetophenone and the Implications for a Synergistic Lithium–Magnesium–Zinc Activation

Abstract: Numerous organic transformations rely on organozinc compounds made through salt‐metathesis (exchange) reactions from organolithium or Grignard reagents with a suitable zinc precursor. By combining X‐ray crystallography, NMR spectroscopy and DFT calculations, this study sheds new light on the constitution of the organometallic species involved in this important synthetic tool. Investigations into the metathesis reactions of equimolar amounts of Grignard reagents (RMgX) and ZnCl2 in THF led to the isolation of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 102 publications
0
12
0
1
Order By: Relevance
“…Recently, we have shown that MgCl 2 greatly enhances the reactivity of organozinc reagents towards carbonyl derivatives. [5i] In fact both MgCl 2 and LiCl [18] increase the intrinsic reactivity of organozinc reagents by boosting their nucleophilicity as well as the electrophilicity of the carbonyl compound (Lewis acid activation). [19] Such activation is also observed for arylzinc pivalates of type 3.…”
mentioning
confidence: 99%
“…Recently, we have shown that MgCl 2 greatly enhances the reactivity of organozinc reagents towards carbonyl derivatives. [5i] In fact both MgCl 2 and LiCl [18] increase the intrinsic reactivity of organozinc reagents by boosting their nucleophilicity as well as the electrophilicity of the carbonyl compound (Lewis acid activation). [19] Such activation is also observed for arylzinc pivalates of type 3.…”
mentioning
confidence: 99%
“…The previous investigation evaluating the effect of ligands clearly underlined influences of such compounds on the reactivity of organolithiums . In this context, “salt effects” have attracted significant interest in recent years, leading to comprehensive spectroscopic and theoretical investigations, more specifically in organolithium chemistry where the effects of lithium halides are commonly encountered . Lithium salts are undoubtedly among the most widely studied salts, being ubiquitous in a large number of lithiation reactions – either because they are generated in the reaction, or because they are involuntarily brought by a contaminated commercial source.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the presence of a multimetallic synergistic effect in the reaction process 12. In addition, the role of LiCl may also involve (1) breaking the aggregation of ArZnCl with the coproduct of MgCl 2 through the formation of a trimetallic adduct, and (2) enhancing the reactivity of the zinc reagents by forming more nucleophilic zincates 9b,12,13. When the reaction time was shortened to 12 h, the reaction still gave a 99 % yield of the product (Table 1, entry 18).…”
Section: Resultsmentioning
confidence: 99%